Development of DORA Media (Interactive Video) on the Coordination System Materials of Grade XI Senior High School - Riska Sofiani Nurhidayah; Eva Nurul Malahayati; Devita Sulistiana (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
This study aims to determine the feasibility and response of teachers and students to learning media DORA (Interactive Video) on the material of the coordination system applied to grade XI Senior High School. The approach used is qualitative with the type of development research (RnD) 4-D model which is limited to the dissemination stage. Retrieval of research data using a feasibility questionnaire and a response questionnaire. The data analysis technique used is descriptive statistics. The results showed that (1) learning media DORA (Interactive Video) is very feasible based on the assessment of media experts by 86%, material experts by 91%, language experts by 84%, and a readability questionnaire from the teacher by 85%, and students amounting to 83.89%; (2) the teacher's response is said to be very good with a percentage of 85%, and the response of students is said to be good with a percentage of 78.96%. Learning media DORA (Interactive Video) is packaged in the form of an android application so that it can be implemented in the classroom and online learning.Abstrak Penelitian ini bertujuan untuk mengetahui kelayakan serta respon guru dan peserta didik terhadap media pembelajaran DORA (Video Interaktif) pada materi sistem koordinasi yang diterapkan pada kelas XI SMA/MA. Pendekatan yang digunakan yaitu pendekatan kualitatif dengan jenis penelitian pengembangan (RnD) model 4-D yang dibatasi tidak sampai pada tahap desiminasi. Pengambilan data penelitian menggunakan angket kelayakan dan angket respon. Teknik analisis data yang digunakan adalah deskriptif statistik. Hasil penelitian menunjukkan bahwa (1) media pembelajaran DORA (Video Interaktif) sangat layak berdasarkan penilaian dari para ahli media sebesar 86%, ahli materi sebesar 91%, ahli Bahasa sebesar 84%, serta angket keterbacaan dari guru sebesar 85%, dan peserta didik sebesar 83,89%; (2) respon guru dikatakan sangat baik dengan presentase sebesar 85% dan respon peserta didik dikatakan baik dengan presentase sebesar 78,96%. Media pembelajaran DORA (Video Interaktif) dikemas dalam bentuk aplikasi android sehingga dapat diimplementasikan dalam pembelajaran dikelas maupun daring.